Association of physical activity and fine motor performance in individuals with type 2 diabetes mellitus and/or non-alcoholic fatty liver disease. (12th December 2023) - Weinstein, Ali A.; Ngo, Dung; de Avila, Leyla; Price, Jillian K.; Golabi, Pegah; Austin, Patrick; Escheik, Carey; Gerber, Lynn H.; Younossi, Zobair M.
Abstract: Background: Fine motor performance may serve as an early warning sign for reduced cognitive function. Physical activity can help preserve cognitive function; however, the relationship between fine motor performance and physical activity is not well understood. Therefore, this study examined the relationship between fine motor performance and physical activity in individuals at risk for developing cognitive impairment (those with diabetes and/or non-alcoholic fatty liver disease (NAFLD)). Patients and methods: Individuals aged 25–69 with and without diabetes and NAFLD were enrolled. For this cross-sectional study, all participants completed the Human Activity Profile and fine motor performance tasks (Grooved Pegboard Test and Trail Making Test). Results: There were 93 participants in the study (NAFLD only ( n  = 29); diabetes + NAFLD ( n  = 34), controls ( n  = 30)). Individuals with both diabetes and NAFLD were less physically active and performed slower on the fine motor performance task. A statistically significant correlation was found between physical activity and motor speed among those with NAFLD only ( r  = 0.436, p <.05), which remained statistically significant after controlling for body mass index ( r  = 0.385; p <.05). Conclusions: This study suggests that those with diabetes + NAFLD have lower levels of physical activity and slower fine motor performance. The relationship between physical activity and fine motor performance was only statistically significant in the group of individuals with NAFLD only. Future research needs to explore the mechanisms that impact fine motor performance and physical activity in individuals at risk for mild cognitive impairment. Individuals with diabetes and/or NAFLD should be identified, advised and encouraged to engage in physical activity. Key Messages: Those with NAFLD and T2DM have lower levels of physical activity and slower fine motor performance compared to controls and those with NAFLD only. Future research needs to explore the mechanisms that impact fine motor performance and physical activity in those with T2DM with or without NAFLD. Individuals with impaired fine motor performance should be identified and encouraged to engage in physical activity.